Enhancing Elementary Teachers’ Competence: Collaborative Learning in the Organized Training System (CarLOS) in Dairi - Rajagukguk, Jonson; Rahman, Arif; Siallagan, Sahala; Lubis, M. Joharis (Journal of Posthumanism, 2025)
This study aims to evaluate the characteristics, feasibility, and effectiveness of the CarLOS-based training management model in enhancing the pedagogical competencies of elementary school (SD) teachers in Dairi Regency. Utilizing the ADDIE approach—analysis, design, development, implementation, and evaluation—the research was conducted from June 2023 to February 2024, involving 100 teachers and two model trials. Initially validated by experts and then tested with users, all research instruments passed validity and reliability checks. Key characteristics of the CarLOS model include: a) Collaborative Design with active participant involvement; b) Adaptive Flexibility to accommodate changes; c) Active Collaborative Learning promoting cooperation and knowledge exchange; d) Technology-Enhanced Collaborative Learning integrating technology; e) Theory Integration combining the Collaborative Learning Model and Inductive Training Model; and f) Inclusive Participation to ensure broad involvement. The model’s feasibility was rated highly, with a 94% average score from experts and 88.25% from user trials. Its effectiveness was confirmed through paired sample t-tests, which showed significant improvement in pedagogical competencies, with N-Gain scores of 76.08% in limited trials and 77.87% in extensive trials. These results indicate that the CarLOS model is highly effective in enhancing the pedagogical competencies of SD teachers in Dairi Regency, with an overall user assessment score of 94.49%. The model not only improves pedagogical skills but also enhances the overall learning approach in elementary schools.